2014
DOI: 10.1080/14680629.2014.908138
|View full text |Cite
|
Sign up to set email alerts
|

Loading capacity strengthening to cement-stabilised crushed gravel using reinforced wire mesh

Abstract: Sanjeev Adhikari (2014) Loading capacity strengthening to cement-stabilised crushed gravel using reinforced wire mesh, Road Materials and Pavement Design, 15:3, 733-745, Settlement and non-uniform deformation of frozen soil subgrade introduce fatal cracks on semirigid base asphalt pavements. This research aims to use reinforced wire mesh to reduce serious cracks on semi-rigid asphalt pavements in frozen regions. Three impact factors, diameter and interval as well as two types of wire mesh have been analysed by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…The cement-stabilized gravel (CSG) is being used widely as a typical semi-rigid base material [ 1 , 2 , 3 , 4 ]. On account of its aggregate gradation and hydration of the cementing material, CSG contains a considerable number of pores in its structure [ 5 , 6 ]. A certain number of cracks will develop in a CSG base once it is laid, forming open channels [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…The cement-stabilized gravel (CSG) is being used widely as a typical semi-rigid base material [ 1 , 2 , 3 , 4 ]. On account of its aggregate gradation and hydration of the cementing material, CSG contains a considerable number of pores in its structure [ 5 , 6 ]. A certain number of cracks will develop in a CSG base once it is laid, forming open channels [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Based on this, numerous researchers have conducted related research on the road performance of cement-stabilized materials [16]. Ma et al found that the crushed gravel processed in accordance with the required specifications can effectively reduce the crushing phenomenon during construction and has a rough and irregular fracture surface, which can effectively improve its adhesion to the cement slurry [17]. Lin et al [18] and Wang et al [19] used 6.5% overdose cement and 2% antishrinking agent and a vibration compaction method to form a cement-stabilized crushed gravel (CSCG) mixture to improve the durability of the CSCG base.…”
Section: Introductionmentioning
confidence: 99%
“…Sun et al studied the strength, modulus, frost resistance, water stability, and other technical properties of cement-stabilized iron ore tailings gravel in highway applications [23]. Ma et al used reinforced mesh to enhance the carrying capacity of CSCG [17]. Han et al conducted experimental research on the gradation and road performance of cement and fly ash-stabilized macadam based on the theory of mixture gradation [24].…”
Section: Introductionmentioning
confidence: 99%